Assessing the impact of educational methods on influenza vaccine uptake and patient knowledge and attitudes: a randomised controlled trial - Pei Lin Hu; Eileen Yi Ling Koh; Jolene Shi Han Tay; Valerie Xin-Bei Chan; Shermin Shi Min Goh; Sinead Zhen Wang (Singapore Medical Journal)
Introduction: Although influenza vaccination reduces rates of pneumonia, hospitalisation and mortality, influenza vaccination uptake remains low in older patients. The primary aim was to compare individualised counselling with educational pamphlets alone in improving influenza vaccination uptake. The secondary aims were to evaluate knowledge and attitudes towards influenza vaccination and factors influencing uptake. Methods: A randomised controlled study was conducted in two government polyclinics with 160 participants per arm. Patients aged 65 years and above attending for doctor consultation were recruited. All participants received an educational pamphlet on influenza vaccination. The intervention group received additional face-to-face counselling. Participants filled a pre- and postintervention questionnaire assessing knowledge of influenza and attitudes towards the vaccine. Follow-up calls and verification of electronic records was done at three months to determine actual vaccine uptake. Results: At three months, 16 (10%) patients in the intervention group and 20 (12.5%) patients in the control group had completed influenza vaccination (P = 0.48). Factors positively associated with vaccine uptake were willingness to receive vaccination immediately after intervention (adjusted odds ratio [OR] 12.15, 95% confidence interval [CI] 4.42–33.38), and male gender (adjusted OR 2.96, 95% CI 1.23–7.12). Individualised counselling was more effective in improving knowledge (P < 0.01). Overall knowledge scores did not influence actual vaccine uptake rates. (adjusted OR 1.10 [0.90–1.3]). Conclusion: Both arms of patient education increased uptake of influenza vaccination. Individualised counselling was not superior to pamphlets alone in improving uptake. Performing vaccination at the initial point of contact improves actual uptake rates.